Preventive Behavior Towards Maya Index at DHF Endemic Area - Pratiwi, Tiwik Suci; Wikurendra, Edza Aria; Yudhastuti, Ririh; Mirasa, Yudhied Agung (Jurnal kesehatan lingkungan (Surabaya. Online), 2021)
Introduction: Primary health care Putat Jaya is an area with the highest number of DHF cases out of the three primary health care in Sawahan District, Surabaya City. The number of breeding sites for mosquitoes and the density of larvae can be the risk factors that affect mosquitoes’ spread. Maya Index is an indicator to measure the number of water reservoirs used as breeding grounds for mosquitoes. This study aims to analyze behavioral factors towards virtual index in dengue-endemic areas in the Primary health care Putat Jaya Surabaya. Methods: The research used observational type with a cross-sectional design. The population of this study was all houses in the highest endemic. The sample consisted of 100 houses taken randomly, with research variables including mosquito nests eradication behavior and Maya Index status. Data collection used questionnaires and direct observation. The data were presented in the form of distribution tables and statistically analyzed with the chi-square test. Results and Discussion: The results showed the Maya Index of 74 houses in the high category. There was a significant relationship between the respondent’s behavior (knowledge, attitude, action) and the Maya Index. Analysis of the relationship between respondents’ knowledge and Maya Index showed that the p-value = 0.00. Analysis of the relationship between respondents’ attitudes with the Maya Index shows that p-value = 0.02. Furthermore, there was a significant relationship between the respondent’s actions and the Maya Index with a p-value = 0.03. Conclusion: Based on the results of research, community behavior (Knowledge, Attitude, Action) has a significant relationship with the Maya Index level, and the high virtual index affects the risk level of DHF transmission. Knowledge was the most potential factor that affected the Maya Index. It is suggested that the community will often strive to eradicate mosquito nests independently and regularly as well as increase community knowledge with the help of community health center officers regarding the eradication of mosquito nets.